Design of Room Lighting Electric Power Savings Using PIR Sensor - Kokaa, Arnoldus V.; Setiawan, Aries Boedi; Aditya, Mochammad Viky; Bayhaky, Bayhaky (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The current lighting system is one of the big electricity usage. With the lights, human activities can last 24 hours non-stop. The higher the intensity of activities that require lighting, the energy used is also getting higher and higher. For that we need to try to save energy in lighting system. In general, lighting arrangements only use the principle on or off regardless of activity in the room. This leads to inefficient use of electrical energy. From that thought then designed to build room power saving lamps by using PIR sensor is more efficient because the igniter lights the room is controlled automatically. The existence of the subject will be detected using a Passive Infra Red sensor (PIR) applied by the microcontroller. The MOSFET driver is used as a switch. So the lights will light up brightly as long as there are subjects in the room, and the lights will dim back when the subject leaves the room. The subject is focused on humans. With the creation of this system is expected to save electrical energy.